2018
DOI: 10.1177/1526602818766864
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Outcomes of the Nellix EndoVascular Aneurysm Sealing System for Treatment of Abdominal Aortic Aneurysms

Abstract: Purpose: To analyze the 2-year outcomes of endovascular aneurysm sealing (EVAS) according to 2 versions of the instructions for use (IFU). Methods: A retrospective study was conducted involving 355 consecutive patients treated with the first-generation EVAS device from April 2013 to December 31, 2015, at 3 high-volume centers. Out of 355 patients treated with EVAS, 264 were elective asymptomatic infrarenal EVAS procedures suitable for analysis. In this cohort, 168 (63.3%) patients were treated within the IFU 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 40 publications
2
52
2
Order By: Relevance
“…128,129 Thus, improvements in the technique and longer follow-up are necessary before it can be implemented on a large scale and its adoption with the sole purpose of reducing the rate of T2EL is not justified by current evidence. 130 Also, whether the best stent graft to prevent T2EL would combine the polymer sacs from Nellix with a conventional stent graft that uses self-expanding covered stents that generate radial force for adequate proximal sealing remains a topic to investigate.…”
Section: Preventionmentioning
confidence: 99%
“…128,129 Thus, improvements in the technique and longer follow-up are necessary before it can be implemented on a large scale and its adoption with the sole purpose of reducing the rate of T2EL is not justified by current evidence. 130 Also, whether the best stent graft to prevent T2EL would combine the polymer sacs from Nellix with a conventional stent graft that uses self-expanding covered stents that generate radial force for adequate proximal sealing remains a topic to investigate.…”
Section: Preventionmentioning
confidence: 99%
“…The full texts of the remaining 38 articles were obtained and assessed for eligibility. Fourteen studies met the inclusion criteria of our study and were included in qualitative and quantitative synthesis 821…”
Section: Resultsmentioning
confidence: 99%
“…The recruitment period in all but one study was 1 year or more 17. Four studies10,12,13,16 reported 1-year outcomes, while the remaining studies reported longer follow-up outcomes 8,9,11,14,15,1821. The weighted mean follow-up was 11.6±5.4 months.…”
Section: Resultsmentioning
confidence: 99%
“…The Nellix Endovascular sealing system (Endologix, Irvine, California) is an investigational device that has a femoral access diameter requirement of at least 7-mm and involves injecting a biostable polyethylene glycol polymer into "endobags," which allow exclusion of the aneurysm and prevention of type 2 endoleaks [51]. It has been successfully used in unilateral and bilateral common iliac artery occlusive disease ranging from 70% stenosis to complete occlusion [52].…”
Section: New Generation Of Aortic Endograftsmentioning
confidence: 99%